Biolubricant synthesis using immobilised lipase: Process optimisation of trimethylolpropane oleate production - Orellana Coca Åkerman, Cecilia; Hagström, Anna; Bornadel, Amin; Karlsson, Stefan; Hatti-Kaul, Rajni (Process Biochemistry, 2011)
Synthetic esters based on polyols and fatty acids possess suitable technical and ecological properties for applications as biolubricants, and can replace the mineral oil based lubricants in several applications. In this work, the synthesis of trimethylolpropane (TMP) esters with oleic acid using immobilised lipase B from Candida antarctica (Novozym (R) 435) has been studied. TMP-trioleate has suitable properties for use as hydraulic fluids, especially at extreme temperatures. The effect of different reaction parameters on the reaction efficiency has been evaluated. The study showed that the formation of the triester product was facilitated at high temperature and biocatalyst concentration, as well as stoichiometric amounts of oleic acid and TMP. The product with the highest triester content exhibited the lowest pour point (-42 degrees C). The stability of the biocatalyst was however limited at high temperature and polyol concentration. Loss of activity during recycling of the biocatalyst at 70 degrees C was reduced to some extent by washing it with 2-propanol prior to subsequent run. (C) 2011 Elsevier Ltd. All rights reserved.